In Situ Reconstructed Zn doped FexNi(1−x)OOH Catalyst for Efficient and Ultrastable Oxygen Evolution Reaction at High Current Densities. Issue 37 (12th August 2022) - Zhang, Xian; Yi, Hao; Jin, Mengtian; Lian, Qing; Huang, Yu; Ai, Zhong; Huang, Runqing; Zuo, Ziteng; Tang, Chunmei; Amini, Abbas; Jia, Feifei; Song, Shaoxian; et al.
Abstract: Developing FeOOH as a robust electrocatalyst for high output oxygen evolution reaction (OER) remains challenging due to its low conductivity and dissolvability in alkaline conditions. Herein, it is demonstrated that the robust and high output Zn doped NiOOH‐FeOOH (Zn‐Fe x Ni(1‐ x ) )OOH catalyst can be derived by electro‐oxidation‐induced reconstruction from the pre‐electrocatalyst of Zn modified Ni metal/FeOOH film supported by nickel foam (NF). In situ Raman and ex situ characterizations elucidate that the pre‐electrocatalyst undergoes dynamic reconstruction occurring on both the catalyst surface and underneath metal support during the OER process. That involves the Fe dissolution‐redeposition and the merge of Zn doped FeOOH with in situ generated NiOOH from NF support and NiZn alloy nanoparticles. Benefiting from the Zn doping and the covalence interaction of FeOOH‐NiOOH, the reconstructed electrode shows superior corrosion resistance, and enhanced catalytic activity as well as bonding force at the catalyst‐support interface. Together with the feature of superaerophobic surface, the reconstructed electrode only requires an overpotential of 330 mV at a high‐current‐density of 1000 mA cm −2 and maintains 97% of its initial activity after 1000 h. This work provides an in‐depth understanding of electrocatalyst reconstruction during the OER process, which facilitates the design of high‐performance OER catalysts. Abstract : Electro‐oxidation‐induced reconstruction is reported for transforming primary nickel foam (NF) supported Zn‐modified Ni metal/FeOOH film (Zn‐(Ni/FeOOH)@NF) into the robust and high output Zn‐doped NiOOH‐FeOOH@NF (Zn‐Fe x Ni(1− x ) OOH@NF). The reconstructed electrode exhibits remarkable oxygen evolution reaction activity and stability under industrial conditions.